Adopting a systems view of disrupting crisis-driven food insecurity. (October 2022) - Sharma, A.; Lin, M.; Okumus, B.; Kesa, H.; Jeyakumar, A.; Impellitteri, K.
Abstract: Objectives: During the COVID crisis, the incidence of food insecurity worsened around the globe. We were reminded that: food insecurity existed before COVID, worsened during this crisis, and will unfortunately be a persistent phenomenon in the post-COVID world. It is evident that to counter this public health threat, systematic changes will need to happen. In this short communication, we introduce the notion of a systems-oriented framework that can guide appropriate actions for us to disrupt future food insecurity crises. Study design: This short communication identifies preliminary observations based on relevant past studies that documented the impact of COVID-19 on food insecurity, and the researchers' conceptualization of a framework on how we may address future crisis-driven food insecurity challenges. Methods: Systems-oriented framework was conceptualized based on preliminary observations in studies that investigated food insecurity during the COVID-19 pandemic. Results: This short communication explores the notion of a systems-oriented framework as a guide to future action to prevent crisis-driven food insecurity. Conclusions: The systems-oriented framework emphasizes the importance of action across macro, meso, and micro levels, and synchronization to maximize synergies.